Remap NHT learning model integrates scientific literacy and critical thinking to enhance students creative thinking - Irawan, Ferry; Zakiyah R, Nur (STKIP Persada Khatulistiwa Sintang, 2025)
Students' scientific literacy skills help them analyze and evaluate each scientific subject. It is predicted that scientific literacy skills will help students improve their communication abilities as well. This study evaluated the correlation between scientific literacy and Critical thinking skills in developing creative thinking skills using the Remap-NHT learning model. The study was quasi-experimental since it employed a non-equivalent pretest-post-test control group design and included 122 eleventh-grade students at SMAN 4 Soppeng during the 2023/2024 academic year. The participants were divided into three groups. An essay test assessed every variable. The findings indicated that (1) there was a significant correlation between scientific literacy skills and creative thinking skills; (2) there was a significant correlation between Critical thinking skills and creative thinking skills; and (3) there was a significant correlation between scientific literacy skills and Critical thinking skills. The regression equation showed Y= 0,228*X1+0.995*X2+21,645. Based on the findings, it can be concluded that Remap-NHT can be utilized to improve students' scientific literacy, communication, and creative thinking skills, all of which are demonstrated to be connected.